teachers' reported accounts on teaching grammar at kresna institute in pare - Nizar Al Faris (Jurnal Penelitian, Pendidikan, dan Pembelajaran, 2022)
Abstract: The purpose of this study was to find out the instructions, strategies, and media used by teachers who teach in the Planet English program at the Kresna Institute. This study used a qualitative research approach and methods and data collection techniques used through interviews, observation, and documentation. The data analysis technique used Creswell’s method which included collecting the data, reading and understanding all of the data, preparing and organizing the data, coding the data, and interpreting the findings. The participants in this study were two teachers who teach the Planet English Program at the Kresna Institute. There were several criteria to become a participant in this research. Among others, namely: a. teachers have extensive teaching experience, at least 3 years. b. the teacher has a good understanding of the material. c. teachers have good teaching skills. The information was obtained from the administrative staff at the Kresna Institute. The findings of this study indicated that 1) The instructions used were the delivery of learning objectives, providing motivation, and good communication or interaction. The instructions. The instructions were used to increase students' interest in learning. There were several things that the teacher does before the learning process begins. These were the delivery of learning objectives, providing motivation, and good communication or interaction. 2) The strategies used were the tutorial program, mapping and stepping, and weekly exams. 3) The media used were whiteboard and three-color markers. Based on the findings, it can be concluded that teaching grammar requires instructions, strategies, and media that are efficient and attract students' interest in learning. This is evidenced by Planet English graduates who have good grammar mastery. The researcher hopes that future researchers can use this research as a data source for further research on teaching English. The researcher suggests that future researchers examine from the student’s point of view about learning English, especially grammar.Keywords: Teaching grammar, instruction, strategy, media